From multi-target anticoagulants to DOACs, and intrinsic coagulation factor inhibitors. (January 2020) - Lin, Lisha; Zhao, Longyan; Gao, Na; Yin, Ronghua; Li, Sujuan; Sun, Huifang; Zhou, Lutan; Zhao, Guiling; Purcell, Steven W.; Zhao, Jinhua
Abstract: From the 1940s to 1990s, heparin and warfarin have been the main anticoagulants for the prevention and treatment of thrombotic events. Since then, LMWHs and fondaparinux proved effective in clinical trials, with better pharmacokinetic profiles and no monitoring requirements. Developed in the early 21st century, DOACs have comparable efficacy to LMWHs, but increase bleeding risk, as the anticoagulant targets (FIIa, FXa) are also essential for physiological hemostasis. In contrast, selective inhibition of the intrinsic coagulation pathway may be a promising strategy for safer antithrombotic treatment. FXII, FXI and FIX inhibitors have produced favorable results in preclinical studies. Notably, intrinsic F.Xase is another promising candidate target, yet to be systematically evaluated. Here, we review the development of anticoagulants, including recent research on intrinsic F.Xase inhibitors, and the revision of coagulation models over time. Studies support optimism for future diversification of anticoagulants, which could offer more reliable and patient-specific therapy.